Implementing upfront mobile digital chest x-ray for tuberculosis diagnosis in India—feasibility and benefits. (15th April 2020) - Datta, Bornali; Prakash, Ashish; Ford, David; Tripathy, Jaya Prasad; Goyal, Pinky; Singh, Shreya; Singh, Veena; Jaiswal, Anand; Trehan, Naresh
Abstract: Background: The Tuberculosis (TB) Control Program in India changed the TB diagnostic algorithm and recommended sputum testing and chest x-ray (CXR) for presumptive TB up front. There is no experience of testing this algorithm in routine field settings. Methods: In a public–private partnership (PPP), a private hospital provided mobile digital CXR services (mounted on a van) to complement the existing diagnostic services of sputum microscopy and GeneXpert testing. All presumptive TB patients (cough >2 weeks) underwent CXR and sputum microscopy, and GeneXpert testing if eligible (smear-negative CXR suggestive of TB). Results: All 2973 presumptive TB patients underwent CXR and sputum microscopy; 471 (15.8%) had abnormal CXR findings suggestive of TB, 129 (4.3%) were smear positive and 17 were extrapulmonary TB. Of the remaining 325 with smear-negative and CXR suggestive of TB, 147 (45.2%) underwent GeneXpert testing, yielding 32 positives (21.8%). Of the remaining 178 with no GeneXpert test done, 106 (60.0%) had CXR definitely suggesting TB (clinically diagnosed TB). Thus a total of 284 cases of TB (161 microbiologically confirmed, 106 clinically diagnosed, 17 extrapulmonary TB) were identified, giving a potential diagnostic yield of 19.6%. Conclusions: Systematic screening with mobile digital X-ray service via a PPP model integrated into the national program is feasible and scalable with a high yield.